2011
DOI: 10.1021/je101040p
|View full text |Cite
|
Sign up to set email alerts
|

Solubilities of Pharmaceutical Compounds in Ionic Liquids

Abstract: The solubilities of paracetamol and ibuprofen were determined in two different ionic liquids at temperatures of 298.15 K, 308.15 K, 318.15 K, 328.15 K, and 338.15 K. The ionic liquids selected were 1-butyl-3-methylimidazolium hexafluorophosphate [BMIM][PF 6 ] and 1-hexyl-3-methylimidazolium hexafluorophosphate [HMIM] [PF 6 ]. In addition, solubility data for paracetamol and ibuprofen in water are reported at the same temperatures extending the data commonly reported in pharmaceutical reference texts. For all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
94
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 28 publications
0
94
0
Order By: Relevance
“…To avoid the possible atomic coordinate overlap at the initial state, each system first was energy minimized prior to a short NVT MD simulation of 500 ps. Next, an NPT MD simulation of 5 ns was performed to maintain the temperature at 338.15 K and the pressure at 1.0 atm, which was consistent with the experimental dissolution conditions . Subsequently, an NPT MD simulation of 10 ns was performed for equilibration, and then another NVT MD simulation of 5 ns following the above final configuration from the NPT MD simulation was performed for further equilibration.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the possible atomic coordinate overlap at the initial state, each system first was energy minimized prior to a short NVT MD simulation of 500 ps. Next, an NPT MD simulation of 5 ns was performed to maintain the temperature at 338.15 K and the pressure at 1.0 atm, which was consistent with the experimental dissolution conditions . Subsequently, an NPT MD simulation of 10 ns was performed for equilibration, and then another NVT MD simulation of 5 ns following the above final configuration from the NPT MD simulation was performed for further equilibration.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…Nevertheless, there is no clear explanation for the interaction of cations with drugs in the solvation process despite their importance so far. The underlying molecular‐level mechanism suggested that a rational selection of the IL structure is vital to achieving efficient dissolution and purification of drugs . Actually, there are extremely scarce systematic studies about the influence of cations and anions on the solvation of drugs at present .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both ILs featured the same hydrophobic and weakly interacting anion [PF 6 ] − . The scope of the study was to investigate the potential to use ILs in future crystallization processes of the two pharmaceuticals, by investigating the solubility, whereas the group in a later paper demonstrated the crystallization of acetaminophen from the IL . Although these ILs are commercially available and exhibit favorable properties such as low viscosity, they may not be a very good choice of ILs for the crystallization of this type of pharmaceutical, as the solubilities of most drugs are inherently low.…”
Section: Introductionmentioning
confidence: 99%
“…Their physiocochemical properties can be modified by using different combinations of cations and anions (Armand et al, 2009;Galinski et al, 2006;Ngo et al, 2000). ILs are receiving much attention due to their wide range of applications in pharmaceuticals such as solvents for poorly soluble drugs, drug reservoirs, drug carriers, antimicrobial agents, antibiofilm agents and ionogels (Smith et al, 2011). An IL based microemulsion (ME) have both the advantages of IL and ME, which can overcome the inability of conventional ME to dissolve number of chemicals including hydrophilic and hydrophobic substances.…”
Section: Introductionmentioning
confidence: 99%